CONCEPT OF DIGITALIZATION OF SAILING LINE IN CRITICAL AREA THROUGH FISHING BOAT GENERATED WAVE IDENTIFICATION - Suprayogi, Dedy Triawan; Satria, Dhimas; Haryadi, Haryadi; Nugraha, Kurnia; Abdullah, Syarif; Erwin, Erwin (Trends in Mechanical Engineering Research, 2024)
This paper explores the concept of digitalization in critical sailing lines to manage ship-generated waves (SGW), with a focus on fishing boats. Indonesia, as a maritime nation, faces challenges due to the environmental impact of SGW, such as riverbank erosion, habitat disruption, and damage to marine infrastructure. The proposed digital framework integrates real-time environmental data, including tidal conditions, river currents, and water depth, with vessel parameters like speed and GPS tracking. This system aims to provide accessible information through websites and smartphone applications, enabling safer and more efficient navigation. The results highlight the importance of digitalization in enhancing maritime safety, reducing environmental damage, and improving operational efficiency for fishermen and port operators.